PERANAN AKURASI SISTEM KOMPUTER HOTEL DI FRONT OFFICE DEPARTEMENT DALAM MENINGKATKAN KEPUASAN TAMU DI THE BALAVA HOTEL MALANG - fitria earlike anwar sani (Jurnal Pariwisata Pesona, 2016)
Front Office is where the provision of information for guests were in the hotel from arranging their departure, including managing payments during their stay at the hotel. To facilitate the work of Front Office, the hotel uses a system called the Emerald System. System as one of the leading framework for managing information technology control serves to bring together all the needs of management by bridging existing dividing business risks, control needs and technical issues. According to the results of questionnaires computer system in The Balava Hotel still not accurately be seen from the number of respondents who answered "yes" by 30% and "No" as much as 70% this proves that the system Emerald distractions that affect employee performance and create a long wait so the service provided front office employees less than the maximum. While variable satisfaction of the guests at The Balava Hotel Malang according to the results of the questionnaire can be inferred from the number of respondents who answered "Yes" as much as 49% and "No" as much as 51% gained a lot of complaining when the administrative process at the time of check-in and check-out, this illustrates that the front office employees still can not do a service desired by the guest.